Political activism before the premiere: indigenous audiovisual production, knowledge otherwise and gender complementarity in the Wiwa film Ushui (2016)
ABSTRACT: Audiovisual production by indigenous collectives around the world has been growing for decades. Academic analyses disagree on whether the films express an alterity that has never been subsumed by Western modernity, or just confirm that ethnic communicators are as influenced by modernity as any other audiovisual production collective. This article develops a critique of these latter scholarly analyses, because they mostly focus on end products, not on the situated analysis of their contexts, the production processes, the intercultural interactions and knowledge otherwise that result in the films. We focus on the production process of the film Ushui, created by the indigenous Wiwa people of Colombia. We show that although there are no pure, totally uncolonised spaces anymore, the breadth of cosmologies present in Latin America and many other regions of the world-system has never been fully subsumed. The analysis of the making of Ushui allows us to witness the everyday expression of the cosmo-experiences of the Wiwa people and the way film-making becomes more of an organisational and political means for them than the artistic, genre-defying, alterity-proving vehicle that academic scholars commonly discuss.